2017
DOI: 10.1007/978-1-4939-7357-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Tools to Measure Cell Health and Cytotoxicity Using High Content Imaging and Analysis

Abstract: High content screening (HCS)-based multiparametric measurements are very useful in early toxicity testing and safety assessment during drug development, and useful in evaluating the impact from new food supplements and environmental toxicants. Mitochondrial membrane potential, plasma membrane permeability, oxidative stress, phosphoplipidosis, and steatosis are a few of the important markers routinely studied for the assessment of drug-induced liver injury and toxicity. Mitochondrial dysfunction leads to oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Endpoints and the multiplex fluorescent staining used are described in Table 1 and below. Assays were conducted based on modifications to previously described standardized methods or strictly following fluorescent dye manufacturers’ protocols [ 48 , 49 ]. If recommended by dye manufacturer or to reduce high background signal, stained cells were washed with 37 °C fresh culture medium then imaged in clear Fluorobrite DMEM (ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
“…Endpoints and the multiplex fluorescent staining used are described in Table 1 and below. Assays were conducted based on modifications to previously described standardized methods or strictly following fluorescent dye manufacturers’ protocols [ 48 , 49 ]. If recommended by dye manufacturer or to reduce high background signal, stained cells were washed with 37 °C fresh culture medium then imaged in clear Fluorobrite DMEM (ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
“…Research with bipolar patients and animal models observed a reduction in TCA cycle enzymes (Lee et al, 2007;Valvassori et al, 2013). In oxidative stress, it is essential to note that mitochondria are the primary source of free radicals, and are generated mainly through the ETC, during the energy production from glucose and oxygen, it generates oxidative stress (Barbosa et al, 2010;Mandavilli et al, 2018). Initially, we will describe the main processes, functions, and losses in oxidative stress, and later, the changes that occur in BD, which are related to the section on biomarkers.…”
Section: Energy Deficits In Neuronal Mitochondria and Its Possible Rementioning
confidence: 99%
“…Notably, hypoxic areas in tumours often lead to lower efficiency of radio-therapies [6]. The investigation of hypoxia is challenging to establish due to the low availability of sensitive fluorescent dyes [7], explicitly measuring the activity of hypoxic cells.…”
Section: Introductionmentioning
confidence: 99%